The impact of the COVID-19 pandemic on health-care delivery system for other diseases and antimicrobial resistance threat in India - Debjit Chakraborty; Agniva Majumdar; Falguni Debnath; Somnath Naskar; Shanta Dutta (Wolters Kluwer Medknow Publications, 2023)
India's health-care delivery is challenged with different inequalities and theelivery is challenged with different inequalities and the dual burden of communicable and noncommunicable diseases. Lockdown posed negative effects on the growth and economy of the country; simultaneously, some positive effects, like increased health consciousness and adoption of hygienic practices, were also there. Health-care delivery system faced tremendous challenges in diagnostics, therapeutics, infrastructure for inpatient care, and protection of health-care manpower. During this period, people chose to self medicate which in turn increased the threat of emergence of antimicrobial resistance. Due to shifting priority to COVID from other diseases, resources were shifted to COVID, affecting the management of other acute and chronic diseases. The launching of COVID-19 vaccination campaign showed some hope. However, despite the vaccination drive, strengthening infrastructure, and surveillance system, the devastating second wave could not be avoided due to the conglomeration of the crowd for pilgrimage, election campaign, and tourism in an unrestricted manner. It may be concluded that the fourth wave may be short lasting due to increased herd immunity.